The Seleucid and Hasmonean periods and the apocalyptic worldview : the first Enoch Seminar Nangeroni meeting, Villa Cagnola, Gazzada (June 25-28, 2012) /: the first Enoch Seminar Nangeroni meeting, Villa Cagnola, Gazzada (June 25-28, 2012). (2016) - Unknown
No abstract available